TINGKAT PENGETAHUAN MASYARAKAT TENTANG PENGGUNAAN OBAT TRADISIONAL SEBAGAI PENGOBATAN ALTERNATIF DI DESA IMBANAGARA KABUPATEN CIAMIS - Fuzi Khoirurifa; Ilham Alifiar; Vera Nurviana (BORNEO JOURNAL OF PHARMASCIENTECH, 2020)
Traditional medicine is an ingredient or a compound which comes from animals,plants, herbal preparations (galenic), and minerals that have been used fromgeneration to generation for treatment and can be applied in the communityaccording to the existing norms in their society. Indonesia has unlimited naturalresources and biodiversity, also known as an agricultural country, 40% ofIndonesian people use traditional medicine and 70% of them come from ruralareas. This study aims to discover the level of public knowledge regarding the useof traditional medicine. Methodology used in this research was observational witha cross sectional research design and the sampling technique used was nonrandom sampling with a purposive sampling approach. The number of samplesobtained in this study were 103 respondents who met the inclusion and theexclusion criteria. The results showed that the level of knowledge of the people inDesa Imbanagara regarding traditional medicine was sufficient (48.5%). Thereason of why people in Desa Imbanagara use traditional medicines is because itis easy to get (32%), the purpose of using traditional medicine is to cure suddenor minor illnesses (68.9%), the place or the way to get traditional medicine is in asmall shop (54.4%), the average use of traditional medicine is 2 - 3 days (37.9%),sources of information obtained from family and / or friends (51.5%). Inconclusion, the level of knowledge of the people in Desa Imbanagara regardingtraditional medicine is sufficient.